2021
DOI: 10.1016/j.cnp.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Omitting TMS component from paired associative stimulation with high-frequency PNS: A case series of tetraplegic patients

Abstract: Highlights PNS and motor imagery were applied to 5 patients with tetraplegia. The setup was identical to a previously published PAS study, but TMS was omitted. This intervention slightly improved MMT scores but not functional hand tests. PNS is inferior to PAS, but might be useful for patients with TMS contraindications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Consistent with our previous result (Tolmacheva et al., 2017), we observed that without TMS, the MMT score increase was 59% smaller than that obtained with PAS. In addition, omitting TMS abolished the therapeutic effect on functional hand tests (Pohjonen et al., 2021). The effect on PNS combined to MI on MMT is plausibly explained by the fact that MI activates M1.…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Consistent with our previous result (Tolmacheva et al., 2017), we observed that without TMS, the MMT score increase was 59% smaller than that obtained with PAS. In addition, omitting TMS abolished the therapeutic effect on functional hand tests (Pohjonen et al., 2021). The effect on PNS combined to MI on MMT is plausibly explained by the fact that MI activates M1.…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Indeed, a number of studies have shown that increasing neuronal activity in different models of CNS injuries can promote some level of functional recovery ( Deng et al, 2021 ; Carmel et al, 2013 ; Bachmann et al, 2013 ; Chen et al, 2018 ; Kathe et al, 2022 ). Clinical studies have also demonstrated the beneficial effects on motor recovery of combined corticospinal tract via transcranial magnetic stimulation and lower spinal circuit stimulation using peripheral nerve stimulation ( Shulga et al, 2021 ; Pohjonen et al, 2021 ; Vaalto et al, 2021 ; Pulverenti et al, 2021 ). However, it is still unclear how to best design efficient neurostimulation therapies above the lesion site and which circuit components they should target to enhance the functional gain that is currently still limited.…”
Section: Introductionmentioning
confidence: 99%